Combined Therapy for Distant Metastasis of Sacral Chordoma - Birol Özkal; Can Yaldız; Peyker Temiz; Cüneyt Temiz (Case Reports in Surgery)
Chordomas are known as rare primary malign tumours that have formed from primitive notochord remains. Sacral chordomas grow slowly but locally and aggressively. Chordomas are locally invasive and have low tendency to metastasis and have a poor prognosis in long-term follow-up. Metastasis may be seen in a rate of 5–40% of the chordomas. Metastasis of chordomas is common in liver, lung, lymph nodes, peritoneum, and brain. The treatment approaches, including surgery, have been discussed in the literature before. Susceptibility to radiotherapy and chemotherapy is controversial in these tumours. The success of surgical treatment affects survival directly. In this report, we will report a sacral chordoma case in which an intraperitoneal distant metastasis occurred and discuss the surgical approach.